Level of retirement preparedness of Northern Iloilo Polytechnic State College (NIPSC) teachers relative to their level of financial literacy - Igual, Ayeesha Joy B.; Faminiano, Apple Joy M.; Maupoy, Jamby B.; Pareja, Ann V. (2018)
The lack of financial knowledge has been one of the reasons behind retirement issues faced by many Filipinos. Recent study about retirement preparedness have emerged that most Filipinos are not ready for retirement. The government has also seen that there is an urgency of need for teachers to be taught about financial literacy. Financial Literacy is considered as means to orient teachers of the adverse effects of over borrowing such as not receiving any from retirement. Therefore, this paper aims to measure the level of financial literacy of teachers of Northern Iloilo Polytechnic State College (NIPSC) and evaluate the results on their retirement preparedness. Using the quantitative research method, data was collected using survey questionnaires and analysed by use of Pearson correlational analysis. The hypotheses were then tested using the binary logistic regression. This study reveals that financial literacy has a significant effect on retirement preparedness. Given that respondents are homogenous and low in numbers, future research is suggested with a much diverse population coming from different occupations, industries and institutions. This will help to identify which factors affect financial literacy and retirement preparedness in a much wider scope. It is also suggested that the school and/or government should provide financial education seminar to acquire appropriate level of financial knowledge and understanding.
Research Paper (MMBM) -- [Iloilo City] : University of the Philippines Visayas, April 29, 2018.